Serotype of Foot-and-Mouth Disease Virus in Cattles Circulated in Asia Region Including Indonesia: A Literature Review - Hartaputera, I Nyoman Surya Tri; Setyaningrum, Aisyah; Baiti, Nur; Krisnawati, Matilda; Maheswari, Luh Gede Winda; Batan, I Wayan (Indonesia Medicus Veterinus; Vol 13 (3) 2024, 2024)
Foot-and-mouth disease virus (FMDV) is a highly contagious infectious disease that poses significant economic and agricultural threats to the livestock industry worldwide. It primarily affects animals with split hooves. The disease is endemic in various regions, where livestock farming, particularly of cattle and other split-hooved animals, plays a vital role in the regional economy. The distribution of the seven Foot-and-mouth disease virus (FMDV) serotypes is not uniform. Foot-and-mouth disease virus exhibits wide antigenic variability and is classified into seven serotypes.  Serotype A virus comprises 32 subtypes, while Asia 1 virus is characterized by three antigenic subtypes. For instance, 44 strains of Asian serotype 1 showed genetic variations. Serotype C viruses isolated in Europe and South America were classified into five antigenic subtypes. Among the different serotypes, the SAT-1 serotype demonstrated six topotypes, the SAT-2 serotype contained eleven topotypes, and the SAT-3 serotype contained six topotypes. Multiple topotypes within the serotypes indicate the diverse nature of FMDV strains circulating in various regions. This literature review aims to provide an analysis of the serotypes of FMDV prevalent in Asia with a specific focus on Indonesia. Understanding the genetic and antigenic diversity of FMDV is crucial for developing effective control measures and vaccines. Ongoing surveillance and research efforts are essential to combat the spread of FMD and protect global livestock populations from its devastating impact on agriculture and economies.